Technology for the treatment promotion of adults living with HIV: Positive o Cuidado (Positive the Care) - Vivian Costa Fermo; Francis Solange Vieira Tourinho; Douglas Dyllon Jerônimo de Macedo; Thaís Favero Alves (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to develop a responsive website focused on treatment adherence for adult users living with HIV. Methods: technological study conducted between August and October 2020, in the light of Pierre Lévy's theoretical-philosophical framework, using the Double Diamond Process methodology associated with the five stages of The Elements of User Experience framework. Results: it was developed the responsive website Positive Care (Positive o Cuidado), composed of an initial presentation screen and 13 other screens named: Family Health and You; Undetectable = Untransmissible; Antiretroviral Drugs; Routine Tests; Vaccination; Antiretroviral Delivery; Drug Interactions; Combined Prevention; Support Services; Healthy Life; Family and Reproductive Planning; Covid 19; and Questions, Curiosities, and Myths. Final Considerations: the responsive website was developed based on the software design and programming process and has requirements/functionalities with the potential to strengthen the collective intelligence about HIV and, consequently, to promote treatment adherence by its users.